Tingkat Sistematika Dan Pelayanan Penggunaan E-Filing Terhadap Kepatuhan WP Dimoderasi Pemahaman WP: Tingkat Sistematika Dan Pelayanan Penggunaan E-Filing Terhadap Kepatuhan WP Dimoderasi Pemahaman WP - Fitri Andriani; Retno Wulandari; Supami Wahyu Setiyowati (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
Abstrak This study aims to obtain evidence and explain the effect of the systematic level of e-Filing and the service of using e-Filing on taxpayer compliance, along with understanding taxpayers as a moderating variable. The level of systematics of e-Filing in this study is the level of ease and difficulty for its users. The service using e-Filing in this research is a service provided by the Direktorat Jenderal Pajak (DJP) to taxpayers through the Primary Tax Service Office (KPP), to be able to report SPT online. Research implemented to Individual Taxpayers (WPOP) registered at KPP Pratama Kepanjen. study This is a quantitative research. The information used is data raw (primary), using a survey method to carry out questionnaires. The technique of obtaining a sample using accidental sampling, obtained as many as 75 people. The data analysis method used path analysis with the help of the SmartPLS 3.0 test tool. Based on the test results, it is concluded that (1) the level of systematic use of e-FiIing has no effect on taxpayer compliance. (2) the service using e-FiIing has a positive and significant impact on taxpayer compliance. (3) understanding taxpayer snot can moderate the effect of the systematic level of use of e-FiIing on taxpayer compliance. (4) understanding of taxpayers moderates the effect of service relations using e-FiIing on taxpayer compliance. Kata Kunci: e-filing, compliance, service, taxpayers, understanding